(untitled) (The Shivapuri Journal, 2025)
The rapid advancement of surveillance and reconnaissance technologies has significantly increased battlefield transparency, posing challenges to achieving surprise and deception in modern military operations. This study explores historical and contemporary methods of military deception, evaluates technological advancements that impact operational security, and proposes innovative strategies to counter enhanced surveillance capabilities. By integrating cyber deception, electronic warfare, and psychological operations with traditional tactics, military forces can maintain strategic and operational advantages despite heightened situational awareness. The study’s findings offer critical insights for military strategists adapting to evolving warfare dynamics.